PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR CAMAT KAMBU - La Iba; La Manguntara (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
This study aims to describe the works of employees and human resource development in the Office of Sub-district head of Kambu on Kendari City. Data collection was done through the distribution of questionnaires, documentation and interviews to the respondents. The results showed that the works of employees in the Office of Sub-district head of Kambu on Kendari were still low. This could be seen from the indicators of timeliness of work, compliance with the rules, quality of work, morale, effective communication, ability to give additional value, and responsibility to the assets of organization. In addition, the development of human resources at the Office of Sub-district head of Kambu on Kendari City was also not maximized. This could be seen from indicators of low mastery of concepts, technical skills and moral development. Keywords : development, human resources, the works, employee